Management of Laboratory Facilities in Improving Students’ Learning Achievement of SMP Negeri 4 Kayuagung - Rusmaniar, Rusmaniar (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to analyze the Management of Laboratory Facilities in Improving Student Achievement at SMP Negeri 4 Kayuagung OKI Regency. This type of research is descriptive qualitative research. Data collection tools use interviews, observation, documentation and literature review. Data analysis techniques using descriptive qualitative analysis techniques. The results of the study stated that the management of laboratory facilities in improving student achievement at SMP Negeri 4 Kayuagung OKI Regency was by improving the quality of laboratory management through improving the quality of laboratory services, increasing the role of laboratory human resources and maximizing laboratory infrastructure facilities at SMP Negeri 4 Kayuagung. Obstacles that are procedural in nature fulfill laboratory facilities for public schools which must follow the provisions of the regional government through the RKAS. School financial problems, laboratory administration systems and laboratory management capacity building training. The solution adopted is to involve all school members and school committees to take an active role in efforts to improve the quality of laboratory services. Then provide laboratory management training at SMP Negeri 4 Kayuagung.